Suicide-authors: a deconstructive study - Loman, Lilia (2005)
The purpose of this thesis is to problematize the relationship between suicide and the author. On the basis of a deconstructive approach, it will study the effect of the self-inflicted death of the writer, namely the emergence of a dual figure, the "suicide-author". To deconstruct the suicide-author, this thesis will combine theoretical issues with examples taken from authors who killed themselves, including texts written by the suicides and by their survivors. Such texts will be referred to as "memorial texts" and will constitute a key element in the deconstruction of the figure of the author, namely his/her "posthumous persona".